2021
DOI: 10.3389/feduc.2021.635473
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Implicit Theories of Professional Abilities in the Domain of School Improvement

Abstract: Numerous studies show positive effects of students’ malleable implicit theories of their abilities on their self-regulated learning and learning achievements (Yeager and Dweck, 2012; Burnette et al., 2013), especially when domain-specific implicit theories are assessed (Costa and Faria, 2018). Thinking of school improvement as a collective learning process for the teaching staff, it is reasonable to assume that this relationship also exists on the teacher level. Hence, this study aims to provide answers to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
1
1
0
1
Order By: Relevance
“…Study 2 findings showed that the growth mindset affords the belief that one can learn new skills and apply them to solve pressing problems resulting from suspension of school teaching. This finding resonates with the past finding that teachers with a growth mindset are likely to engage in emotional and motivational regulation activities that enhance their perseverance and selfreinforcement behaviors (Rechsteiner et al, 2021;Zimmerman et al, 2015). Study 2 findings also confirmed Hypothesis 2: through its association with higher taskspecific self-efficacy, having a stronger growth mindset is accompanied by higher life satisfaction.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Study 2 findings showed that the growth mindset affords the belief that one can learn new skills and apply them to solve pressing problems resulting from suspension of school teaching. This finding resonates with the past finding that teachers with a growth mindset are likely to engage in emotional and motivational regulation activities that enhance their perseverance and selfreinforcement behaviors (Rechsteiner et al, 2021;Zimmerman et al, 2015). Study 2 findings also confirmed Hypothesis 2: through its association with higher taskspecific self-efficacy, having a stronger growth mindset is accompanied by higher life satisfaction.…”
Section: Discussionsupporting
confidence: 86%
“…For example, when students learn the growth mindset, they are willing to attempt intellectually challenging advanced-level math courses (Rege et al, 2020). Likewise, teachers who believe that their professional ability is malleable tend to display emotional-motivational regulation behaviors, such as self-learning, goal setting, and monitoring when a new school improvement project is implemented in their schools (Rechsteiner et al, 2021).…”
Section: Growth Mindsetmentioning
confidence: 99%
“…Mevcut araştırmalar incelendiğinde, örtük zekâ teorilerine ilişkin kanıtların çoğunun esasen okul çağındaki çocuklarla veya öğrencilerle yapılan araştırmalar sonucunda elde edildiği görülmektedir (Burnette ve diğerleri, 2013;Costa ve Faria, 2018). Diğer taraftan, birtakım araştırmalar ebeveynlerin ve özellikle öğretmenlerin zekâ, öğrenme veya bilişsel yetenekler hakkında örtük inançlar geliştirdiklerini göstermektedir (Butler, 2000;Dweck, 2006;Bruning ve diğerleri, 2011;Ferrare, 2019;Gutshall, 2016;Matthes ve Stoeger, 2018;Rechsteiner, 2021;Ronkainen ve diğerleri, 2019). Bu açıdan, öğretmenlerin zekânın sabit olduğuna veya geliştirilebileceğine dair örtük inançları, öğrencilerin akademik potansiyelleri üzerinde bir etkendir (Boaler, 2019;Dweck ve Leggett, 1988;Dweck, 2006;Rissanen ve diğerleri, 2016).…”
Section: Problem Durumuunclassified